Minimally Invasive Tubular Retractor Surgery for Intradural Extramedullary Spinal Tumor Reduces Postoperative Degeneration of Paraspinal Muscle - He, Zhexi; Li, Cho Ying; Mak, Calvin Hoi-Kwan; Tse, Tat Shing; Cheung, Fung Ching (Asian Journal of Neurosurgery, 2022)
Background Minimally invasive surgery (MIS) using a tubular retractor has been increasingly utilized in spinal surgery for degenerative conditions with the benefit of paraspinal muscle preservation. This benefit has not been previously reported for intradural extramedullary tumors using the MIS approach. In this study, we aimed to compare the degree of postoperative fatty degeneration in paraspinal muscle between MIS with tubular retractor (MIS) and open laminectomy (Open) for intradural extramedullary spinal tumors.Methods This was a retrospective review conducted in a tertiary neurosurgical center from 2015 to 2019. The degree of paraspinal muscle fatty degeneration, as measured by Goutallier grade on postoperative magnetic resonance imaging (MRI), was analyzed, and the degree of excision, tumor recurrence rate, and chronic pain were compared between the two surgical approaches.Results Among 9 patients in the MIS group and 33 patients in the Open group, the rate of gross total resection was comparable (MIS: 100.0%, Open: 97.0%, p = 1.000). The degree of paraspinal muscle fatty degeneration was significantly reduced in the MIS group (median Goutallier grade 1 in MIS group vs. median Goutallier grade 2 in Open group, p = 0.023). There was no significant difference in the tumor recurrence rate, complication rate, and chronic pain severity. A consistent trend of reduced analgesic consumption was observed in the MIS group, though not statistically significant.Conclusions Minimally invasive tubular retractor surgery is an effective approach for appropriately selected intradural extramedullary spinal tumors with significantly reduced postoperative fatty degeneration in paraspinal muscle.
Keywords: laminectomy; magnetic resonance imaging; minimally invasive surgical procedures; paraspinal muscles; spinal neoplasms